(untitled) (Physical Education, Health and Social Sciences, 2025)
In today’s rapidly evolving world, entrepreneurship is crucial in driving economic development, necessitating a deeper understanding of the factors influencing students’ entrepreneurial intention. Yet, cultivating entrepreneurial intention remains a formidable challenge among university students in Pakistan. This study examines the dynamic interplay between entrepreneurial education, awareness, orientation, and inspiration in shaping entrepreneurial intention, particularly emphasizing the pivotal moderating role of government support. The data from 825 undergraduate final-year business students at ten universities in Pakistan were collected through structured questionnaires. SmartPLS 4 was used for data analysis, testing eight hypotheses based on social cognitive theory. The findings reveal that entrepreneurial education, awareness, orientation and inspiration significantly enhance students’ confidence in establishing their potential entrepreneurial intention. Additionally, the influence of these factors is more pronounced, with the moderating effect of government support positively amplifying entrepreneurial intention. Further, the study delivers actionable insights for policymakers, academicians and industrial patrons to design operational strategies, educational programs, skills-building initiatives, and supportive policies that collectively nurture entrepreneurial intention, paving the way for sustainable socio-economic development.